PENGARUH KOMUNIKASI ORGANISASI DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU (STUDI KASUS PADA GURU SMA NEGERI 94 KALIDERES, JAKARTA) - Jumenah Jumenah (MediaKom : Jurnal Ilmiah Komunikasi, 2018)
The phenomenon of teachers' bad performance in school occurs for the phenomenon of Principals. As the top leader, Principal plays central role in the organizational structure of school. The research object is State High School 94 Jakarta (SMA Negeri 94 Jakarta) because the achievement does not put it among the top schools in West Jakarta and Greater Jakarta and the performance trend stagnant. To know the phenomenon further, the research has greater focus to know the influence between the relationship of organizational communication and leadership styles of the school's Principal towards the teachers' performance particularly in SMA Negeri 94 Jakarta. The research paradigm is positivism. Theories used in the research are the organizational communication, i.e. downward and upward communication as well as the leadership theory (transformational and transactional leadership). The population becomes the sample in the research for less than 100 respondents, i.e. 37 teachers of SMA Negeri 94 Jakarta. The measurement results of K-M-O Measure of Sampling Adequacy are in the range of 0.560 - 0.899; Bartlett's Test of Sphericity is 0.000 and Total Variance is from 70% to 89.125%. The research results also indicate that upward communcation is the strongest (0.874). It also found that the upward communication influences in SMA Negeri 94 Jakarta if compared to the downward communication. Keywords : downward communication, upward communication, transformational leadership, transactional leadership, the teachers' performance